2019
DOI: 10.1002/mrm.28013
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of gradient system response characteristics

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The primary uncertainty in the signal model is coupled to the assumption that gradient system was modeled as a linear time‐invariant system. Previous work showed that the assumption is valid to a certain extent, but may be violated due to for example gradient heating . The second limitation is that we did not perform higher order gradient impulse response measurements, which may induce additional phase errors that we did not account for.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The primary uncertainty in the signal model is coupled to the assumption that gradient system was modeled as a linear time‐invariant system. Previous work showed that the assumption is valid to a certain extent, but may be violated due to for example gradient heating . The second limitation is that we did not perform higher order gradient impulse response measurements, which may induce additional phase errors that we did not account for.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work showed that the assumption is valid to a certain extent, but may be violated due to for example gradient heating. 28,29 The second limitation is that we did not perform higher order gradient impulse response measurements, which may induce additional phase errors that we did not account for. However, including the higher order phase errors in the RF-PC compensation strategy is not straightforward because these errors have heterogeneous spatial distributions.…”
Section: Discussionmentioning
confidence: 99%
“…These can be divided into two components, (a) non-LTI effects such as fluctuations caused by the subject, (b) changes in the GIRF over time. The latter could be addressed by measuring temperature dependent GIRFs (Nussbaum et al, 2018) (Stich et al, 2019). The hardware temperature can easily be assessed via the scanner's temperature monitoring system or using separate temperature sensors and this information can then be used to select the optimal GIRF for each measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The required field measurements for these calibrations may either rely on a dedicated NMR-probe based field camera De Zanche et al, 2008) or on off-the-shelf NMR phantoms (Duyn et al, 1998), with certain trade-offs to measurement precision and acquisition duration (Graedel et al, 2017). To account for the aforementioned dynamic field effects as well, the spiral sequence could be augmented by higher-order field navigators (Splitthoff and Zaitsev, 2009) or a temperature-dependent gradient response model Stich et al, 2019).…”
Section: Signal Model Limitations and Alternativesmentioning
confidence: 99%